THE ROLE OF HUMAN DEVELOPMENT CADRES IN EFFORTS TO PREVENT STUNTING IN JENEPONTO DISTRICT: A QUALITATIVE STUDY - Alam, Syamsul; Rusmin, Muhammad; Aswadi, Aswadi; Syafri, Muhammad (Homes Journal = Hospital Management Studies Journal, 2024)
Backround: The existence of village development cadres is expected to be the spearhead in efforts to control and prevent stunting, as is done by Jeneponto Regency which targets a 19% reduction in stunting prevalence from 48.8% in 2018 to 2023. Objective: This study aims to analyze the role of Human Development Cadres (KPM) in stunting prevention efforts in Jeneponto Regency, Indonesia, and analyze changes in stunting prevalence before and after the existence of KPM. Method: The research method used was qualitative with a descriptive approach, involving KPM as the main informant. Result: The results show that the majority of KPM have carried out their duties, including socializing the stunting prevention convergence policy, collecting data on 1,000 HPK household targets, monitoring stunting prevention services, and coordinating with various parties. Despite this, there are still some KPM who have not fully carried out their duties. In addition, the stunting prevalence data in Jeneponto District shows a decrease from 2019 to 2021, but is still high when compared to the stunting rates at the provincial and national levels. Conclusion: The majority of KPM have been effective in monitoring nutrition deficiency prevention services for 1,000 targeted HPK households in Jeneponto Regency. Although the prevalence of nutrition deficiency decreased to 37.9% in 2021 from 41.11% in 2019, it remains high compared to the national average. The presence of KPM is expected to aid efforts in reducing nutrition deficiency with a focus on data validation and activity planning at the village level.